Enhancing Transformative Learning through 'Setara Daring': A Framework for Optimizing Equivalent Education in Bandung, Indonesia - Iip Saripah; Joni Rahmat Pramudia; Jajat S Ardiwinata; Gumpanat Boriboon (Universitas Negeri Semarang, 2025)
Background: Transformative learning is a learning process that 'brings' learners closer to reality, presenting critical-reflective knowledge, by positioning the teacher more as a facilitator to guide and encourage that process. Online learning has become a choice for face-to-face learning systems in the Digital Era using Learning Management Systems (LMS) to support learning achievements. Research Objectives: The ultimate goal to be achieved in this research is the emergence of a new product on the transformative learning model assisted by the LMS